Estratégias de forrageamento do muriqui-do-norte (Brechyteles hypoxanthus) em um fragmento florestal em Santa Maria de Jetibá, ES - Silva, Mariana Petri da (2010)
The Muriquis (also known as woolly spider monkeys), the biggest non-human primates, are endemic to the Brazilian Atlantic Forest and have suffered over the centuries, with the intense hunting, deforestation and habitat fragmentation. The northern muriqui (Brachyteles hypoxanthus) is critically endangered and can only be found in a few locations of Minas Gerais and Espírito Santo. Some of these locations are known forest fragments in private lands in the city of Santa Maria de Jetibá, Espírito Santo, and range from 60 to 350 hectare. Little is known about these subpopulations responses to fragmentation and about what factors allow them to present a long-term survival. In this work, I intended to understand the strategies of a group of 13 northern muriquis in a 128-ha forest fragment, related to feeding behavior and space using, in two annual periods with different bioclimatic features (rainy and dry seasons). During 60 days, 30 in each season, I collected data about diet, temporal budget and space use from behavioral scan samples. In the wet season, muriquis spent more time eating fruits, had more traveling hours and less resting hours, apparently maximizing the energy gain. In the dry season, they spent more time feeding on leaves and resting and less time traveling, probably in order to minimize their energy expenditure. In different periods of the year, they ate different plant species, some of them being particularly important in the diet as a whole. They consumed more fruits than expected for such a highly fragmented environment and more unripe fruits than what was found in other studies. About 84% of the total study area was used for foraging in both periods and almost all of this area was used in each season, separately. Knowing that nearly all of the available area has already been used, spatial constraints could be critical to the growth of the group and unripe fruits appear to be widely consumed because of the need for revisitating the food sources. The great floristic diversity in the region, however, is possibly minimizing the effects of a very restricted spatial area, what could allow muriquis to eat more high quality items, as fruits. The increase of the foraging area and the connection with other forest fragments, therefore, seem to be the mainly actions for maintaining the muriqui population in the studied fragment